Romanian validation study of the Boston questionare in patients with carpal tunnel syndrome - Lenuța Bîrsanu; Roxana Covali; Emanuel Matei Roman; Ioan Alexandru Chirap-Mitulschi; Alin Ciubotaru; Mihaela-Dana Turliuc (Balneo and PRM Research Journal)
A single The Boston Carpal Tunnel Questionnaire is a common tool for evaluating the symptoms and function of patients with carpal tunnel syndrome (CTS). It includes the Functional Status Scale and the Symptom Severity Scale. It has been validated in numerous languages and is the most frequently employed patient-reported outcome measure in CTS. The objectives of this study was to evaluate the acceptability, responsiveness, reliability, and validity of the Romanian version. We conducted a two-parts study: the first part involved the translation and cross-cultural adaptation of the The Boston Carpal Tunnel Questionnaire -Romanian version, while the second part was a prospective cohort clinical study that was designed to psychometrically validate the The Boston Carpal Tunnel Questionnaire. We collected demographic characteristics and The Boston Carpal Tunnel Questionnaire scores for thirty-one patients with CTS and performed descriptive and inferential statistics. Our results showed a very good construct validity and excellent reliability (Cronbach's alpha = 0.79) for Boston Carpal Tunnel Questionnaire -Romanian version and the Kaiser-Meyer-Olkin of 0.732, which is considered acceptable (a value above 0.70 is usually statistically significant for factor analysis). Regarding to Bartlett's Approx sphericity test. Chi-Square 641,401, is statistically significant. In conclussion, Boston Carpal Tunnel Questionnaire is a consistent frequently employed patient-reported outcom that can evaluate the symptom burden of CTS and its effect on the ability to conduct daily activities. The structural validity of the BCTQ was investigated in this study among patients with varying degrees of CTS